Pengaruh Pajak Daerah, Retribusi Daerah dan Lain-Lain Pendapatan Asli Daerah yang Sah Terhadap Belanja Daerah di Kabupaten Karawang TAhun 2018-2022 - Rifaldi, Achmad; Jajang Suyaman , Dede; Nurhasanah, Nunung (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to analyze and explain the influence of regional taxes on regional expenditure, to determine the influence of regional levies on regional expenditure, to determine the influence of other legitimate regional original income on regional expenditure. To find out and analyze simultaneously regional taxes, regional levies, other influences of legitimate regional original income on regional expenditure in Karawang district. This research method uses quantitative verification, the sample used is the Karawang district realization report. The analytical test used is multiple linear regression analysis, with partial and simultaneous hypothesis testing. The results of this research show that regional taxes partially have a positive and significant effect on regional spending with a contribution of 42.51% which has a strong relationship with regional spending. Regional levies partially have a positive and significant effect on regional spending with a contribution of 17.06% which has a weak level of relationship with regional spending. Other partially valid PAD does not have a significant but positive effect on regional spending because it has a contribution of 10.96% which has a weak level of relationship with regional spending. Regional taxes, regional levies and others -others: Legal PAD simultaneously has a positive and significant effect on regional spending with a contribution of 50.9%, while heredity is influenced by other people